وسائل التواصل الاجتماعي وأثرها في تنمية الوعي السياسي والأمني والقانوني لدى طلبة جامعة زايد في دولة الإمارات العربية المتحدة - بلوشي، نازلي ناصر علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The purpose of this thesis was to identify the impact of social media in the development of political, security and legal awareness among Zayed University students in the United Arab Emirates. The field survey methodology was used to study a sample of 400 young Emirati students (both sexes) in 2018, and the theoretical input of several arguments is based on some theories. The researcher also tried to explain the issues of study through these statements, and the study reached several results, the most important: the high proportion of people who have always used the means of social communication constantly, as well as the cultural, artistic, educational, health and religious issues. It also highlighted the high percentage of those who have studied the UAE's law for the use of social media and the penalties for using these methods in the wrong way. In addition to the high percentage of those interested in government affairs in the means of social communication, and emphasized the role of means of social communication, whether in propaganda or participation in the elections of the Federal National Council, and highlighted the political implications of the use of social networking sites. On the culture of young people, especially the speed in the transfer of political news followed by freedom of expression, mobilization of public opinion on some political issues, and tried to study the development of several recommendations, including: There should be a legalization of the conditions of these sites and that there should be some kind of censorship, and to coordinate between the various legislative, judicial, administrative, disciplinary and technical branches in order to avoid falling into the circle of electronic crime. The law that protects the security and privacy of individuals must be updated with the adoption of the law against crime. The electronic protection of personal information, and design awareness programs for optimal use and positive social networking sites, and raising awareness of the negative consequences of the use of the individual and society.